2008
DOI: 10.1590/s0004-27302008000900005
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of late-onset male hypogonadism andropause

Abstract: OBJECTIVES: To evaluate which factors influence the laboratorial diagnosis of late-onset male hypogonadism (LOH). METHODS: Total testosterone (TT), SHBG and albumin were measured in 216 men aged 52-84 years. The laboratorial definition of LOH was two values of calculated free testosterone (cFT) <6.5 ng/dl, according to Vermeulen's formula. RESULTS: At the first blood test, cFT was <6.5 ng/dl in 27% of the men. Laboratorial LOH (confirmed by two tests) was present in 19%, but TT levels were low in only 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In another longitudinal study, Liu et al found that the decline in serum testosterone and increase in SHBG with age were comparable across two separate regional Australian populations (11). The influence of age in the testosterone levels was confirmed by Clapauch et al in a study conducted in a cohort of 216 Brazilian men aged 52-84 years (17). In this study, a significant difference in the level of total testosterone was observed between patients < 60 years versus those aged 70 years or more.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In another longitudinal study, Liu et al found that the decline in serum testosterone and increase in SHBG with age were comparable across two separate regional Australian populations (11). The influence of age in the testosterone levels was confirmed by Clapauch et al in a study conducted in a cohort of 216 Brazilian men aged 52-84 years (17). In this study, a significant difference in the level of total testosterone was observed between patients < 60 years versus those aged 70 years or more.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, a significant difference in the level of total testosterone was observed between patients < 60 years versus those aged 70 years or more. In addition to total testosterone, a significant difference in free testosterone levels was also observed between these two age groups (17).…”
Section: Discussionmentioning
confidence: 85%
“…Hypogonadism diagnosis was based in TT levels which may be misleading, as men with "normal" TT may have lower FT and BT. Thus, TT is a poor marker for aging male gonadal function (14), as well as for osteoporosis risk. Bioavailable E2, i.e., E2 not bound to SHBG, has been shown to decrease with age and not to be influenced by the body mass index (BMI), such as TT or total E2.…”
Section: Discussionmentioning
confidence: 99%
“…Colour was auto-referred. This sample has been previously studied in relation to prevalence, clinical (13) and laboratorial hypogonadism diagnosis (14). Hormonal evaluation was performed at the Andrology Sector of Hospital da Lagoa, Health Ministry, Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
“…In principle, the combination of low blood levels of peripheral hormones and inadequately low levels of pituitary hormones (below the upper limit of the reference range) indicates hypopituitarism (30). Table 1 provides a summary of the attempts to evaluate the gonadotropic function.…”
Section: Clinical and Laboratory Characteristics Of Hypogonadismmentioning
confidence: 99%